2018
DOI: 10.1155/2018/3032790
|View full text |Cite
|
Sign up to set email alerts
|

Snakehead Consumption Enhances Wound Healing? From Tradition to Modern Clinical Practice: A Prospective Randomized Controlled Trial

Abstract: Background Snakehead fish (Channa striatus) is a fresh water fish indigenous to many Asia countries and believed to have medical value. Studies showed that it contains all the essential amino acids and fatty acids able to accelerate wound healing and it has antinociceptive effect. However, little human study has been done to assess the effectiveness of Channa striatus in wound healing. A prospective RCT has been conducted on the effect of Channa striatus spray versus placebo on clean wound to assess its pain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…Due to its high levels of essential amino acids and fatty acids, snakeheads are usually used as ingredients in soup, a popular side dish in Asia-Pacific countries (Sahid et al, 2018;Zhang, Zheng, Feng, Shen, Xiong, & Du, 2018). Moreover, snakehead fish has been reported to significantly promote the healing of wounds and burns (Sahid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high levels of essential amino acids and fatty acids, snakeheads are usually used as ingredients in soup, a popular side dish in Asia-Pacific countries (Sahid et al, 2018;Zhang, Zheng, Feng, Shen, Xiong, & Du, 2018). Moreover, snakehead fish has been reported to significantly promote the healing of wounds and burns (Sahid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers believe that a possible factor that plays a role in these results is the part of C. striatus that was used in this study and its compound. The main compounds detected in this C. striatus fillet extract were amino acids (glycine, glutamic acid, arginine, and aspartic acid) and fatty acids (eicosapentaenoic acid, docosahexaenoic acid, palmitic acid, oleic acid, stearic acid, and arachidonic acid), which are important in influencing pain-sensing and wound healing [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies related to the method of stroke induction were carried out by occlusion of internal and external carotid arteries to determine the presence of ischemic stroke areas in brain tissue using the HE routine staining technique. The macroscopic test of the Sprague Dawley rat's brain tissue showed that the rats successfully experienced an ischemic stroke [13].…”
Section: Histological Of Sprague Dawley Rat's Brain Tissue After Ligation Of Internal and External Carotid Arteriesmentioning
confidence: 99%